Pendampingan Pembuatan Pupuk Organik Cair di Desa Wringinrejo Kecamatan Gambiran Kabupaten Banyuwangi - Kurniawati, Emi; Subaktilah, Yani; Indis, Nadhifah Al; Anam Izza Rosyadi, A. Sirojul (Universitas Pahlawan Tuanku Tambusai, 2025)
The problems faced by Wringinrejo Village farmers are the high dependence on chemical fertilizers and the low utilization of household kitchen waste. This exertion was carried out in order to improve the insight and skills of Wringinrejo Village farmers to make liquid organic fertilizer from household kitchen waste in the form of rice washing water as an alternative to chemical fertilizers. In addition, this activity also increases the awareness of participants towards sustainable agriculture. Through a participatory approach, this exertion was carried out in the form of comforting, mentoring, direct practice of making liquid organic fertilizer using simple ingredients including rice washing water, molasses, and EM4 as well as monitoring. The results of the fermentation of liquid organic fertilizer were then tested on durian plants. The results of observations showed that durian plants that were given liquid organic fertilizer grew better, while those that were not given fertilizer grew slowly.